Nutritional composition and physicochemical changes in Maracaju sausage during freezing storage - ANDRADE, Renata Ribeiro Campagnoli; ALTEMIO, Angela Dulce Cavenaghi; SILVA, Maria Ildilene da; SILVA, Valfredo Fiqueira da; MORAES JÚNIOR, Milton Teixeira de; CARDOSO, Cláudia Andréa Lima; GOES, Elenice Souza dos Reis (Food Science and Technology, 2025)
This study characterized Maracaju sausages and evaluated their physicochemical changes during storage for six months under freezing conditions, with a focus on lipid stability. The sausages were purchased immediately after production from three producers affiliated with the Association of Producers of Traditional Maracaju Sausage (APTRALMAR, Mato Grosso do Sul), in the municipality of Maracaju, Mato Grosso do Sul (MS). The centesimal composition and texture profile were consistent across brands, indicating standardization. All the brands exhibited viable aerobic mesophilic microorganism counts above those permitted by law. In terms of color, the a*, b*, and saturation chromas increased up to 90 days, with a subsequent reduction. pH and shear force remained unchanged throughout storage. The highest cooking loss occurred at 120 days. Water retention capacity was lower at 30 and 90 days. The peroxide index was only detected in the first month, while the thiobarbituric acid reactive substance values increased with extended storage. Fatty acid composition remained stable for up to 90 days, with significant reductions in all fatty acids after 120 days. These findings suggest that oxidation processes remain stable over a period of up to 90 days of freezing storage.